Visualizing the social in aquaculture: How social dimension components illustrate the effects of aquaculture across geographic scales. (August 2020) - Krause, Gesche; Billing, Suzannah-Lynn; Dennis, John; Grant, Jon; Fanning, Lucia; Filgueira, Ramón; Miller, Molly; Pérez Agúndez, José Antonio; Stybel, Nardine; Stead, Selina M.; Wawrzynski, Wojciech
Abstract: Until very recently, governments of many countries, as well as their supporting organizations, have primarily addressed the biological, technical and economic aspects of aquaculture. In contrast, social and cultural aspects of aquaculture production have taken a backseat. Drawing on the observation that aquaculture development in Western Societies has largely failed to address these social effects across different scales and contexts, this paper offers a new way of capturing and visualising the diverse social dimensions of aquaculture. It does so by testing the ability to operationalise a set of social dimensions based on categories and indicators put forward by the United Nations, using several case studies across the North Atlantic. Local/regional stakeholder knowledge realms are combined with scientific expert knowledge to assess aquaculture operations against these indicators. The approach indicates that one needs to have a minimum farm size in order to have an impact of a visible scale for the different social dimension categories. While finfish aquaculture seems to be more social impactful than rope mussel farming, the latter can hold important cultural values and contribute to place-based understanding, connecting people with place and identity, thus playing a vital role in maintaining the working waterfront identity. It could be shown that aquaculture boosts a potential significant pull-factor to incentivise people to remain in the area, keeping coastal communities viable. By visualising the social effects of aquaculture, a door may be opened for new narratives on the sustainability of aquaculture that render social license and social acceptability more positive.